Evaluation of genotoxicity of Euphorbia triaculeata Forssk. extract on mice bone marrow cells in vivo - Mohamed, Hanaa Mahmoud (Toxicol Rep, 2018)
Chemotherapeutic agents for cancer are highly toxic to healthy tissues at therapeutic doses and hence alternative medicine avenues are widely researched. Most of the studies on alternative medicine have suggested that Euphorbia plant possesses considerable antitumor and antibacterial properties. The present study was designed to evaluate the in vivo genotoxic effects of Euphorbia triaculeata extract on mice bone marrow cells using chromosomal aberration test and micronucleus assay. This study also deals with the effect of E. triaculeata on the standard drug cyclophosphamide (CP) treatment in mice. Three different doses 250, 500 and 1000 mg/kg body weight were selected. In micronucleus assay, single oral dose administration of Euphorbia triaculeata extract at the three doses did not increase the number of micronucleated polychromatic erythrocytes. Similarly, a single oral administration of Euphorbia triaculeata extract showed no significant changes on mitotic indices or in induction of chromosomal aberrations in mice bone marrow cells. Pretreatment with E. triaculeata extract significantly reduced the clastogenicity of CP. Hence it can be concluded that, E. triaculeata extract showed no significant genotoxic effect on mice bone marrow cells. Under the conditions of this study, it has been demonstrated that the Euphorbia triaculeata extract is not genotoxic and not clastogenic at the concentrations used.